Transporters involved in source to sink partitioning of amino acids and ureides opportunities for crop improvement - Tegeder, Mechthild (Journal of experimental botany, 2014)
In most plant species, amino acids are the predominant chemical forms in which nitrogen is transported. However, in nodulated tropical or subtropical legumes, ureides are the main nitrogen transport compounds. This review describes the partitioning of amino acids and ureides within the plant, and follows their movement from the location of synthesis (source) to the sites of usage (sink). Xylem and phloem connect source and sink organs and serve as routes for long-distance transport of the organic nitrogen. Loading and unloading of these transport pathways might require movement of amino acids and ureides across cell membranes, a task that is mediated by membrane proteins (i.e. transporters) functioning as export or import systems. The current knowledge on amino acid and ureide transporters involved in long-distance transport of nitrogen is provided and their importance for source and sink physiology discussed. The review concludes by exploring possibilities for genetic manipulation of organic nitrogen transporter activities to confer increases in crop productivity